Winner take all: Competition, strategy, and the structure of returns in the internet economy - Noe, T; Parker, G (2005)
In this paper, we develop an economic rationale for the following stylized fact: Web-based firms spend profligately on advertising and marketing and usually lose money. Our rationale is based on the winner-take-all structure of high fixed cost, low marginal cost, markets for information goods. This market structure ensures that market participation and investment policy are highly stochastic. Moreover, if a firm chooses to participate in a Web market, it is optimal to act very aggressively through saturation advertising. Although increases in advertising costs reduce the probability of entry, once the decision to enter is made, firm strategies are insensitive to advertising price. Consistent with empirical studies of the profitability of internet firms (Hand, 2001), our model predicts returns that are highly positively skewed, that is, even the firms that survive the competition for market position have a small chance of huge gains combined with a large probability of very modest returns. In dynamic competition, firms weakened by early rounds are less likely to challenge in subsequent rounds. However, when a challenge is attempted, it is always aggressive. In addition, because large expenditures in the first period produce valuable strategic real options in later periods, which are treated as expenses using traditional accounting methodology, the financial valuation of Internet firms may actually be negatively related to performance when using standard accounting measures of profitability that fail to capitalize these strategic real options.